COOLING AND CONFINEMENT IN LATTICE GAUGE-THEORY - Teper, M (1994)
We investigate what happens to confinement in lattice gauge fields that have been subjected to cooling. We prove that the local character of cooling is by itself enough to ensure that however many cooling sweeps we perform the cooled configurations will continue to be confining, with the usual string tension, at sufficiently large distances. We support the general theoretical arguments with explicit calculations in some simple models as well as with numerical calculations of Polyakov loop correlations. In addition we show that glueball masses can be extracted from cooled configurations in the same way as the string tension. We also compare the relative efficiencies of calculations of the string tension with and without cooling. We find that cooling, while it is an efficient method, possesses no clear advantage when compared to state-of-the-art methods without cooling.